Training Making Videos based on Digital Media Content to Improve Promotion Skills of Tourism Village Managers - Nifa, Kholishotun; Sunardi; Setiawan, Abdul Haris (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Life in this digital era is greatly influenced by technological advances. The sheer volume of technology shows that humans and technology cannot mix. In the 5.0 era, there is the idea that technology will work together with humans to improve the quality of life. One area that will benefit from the community is tourism. To increase tourism promotion, people can discover tourist attractions through digital content. Searching on various digital media, usually called social media, allows people to find tourist attractions through digital content. This conceptual research discusses the use of digital content as a tourism promotion tool. The importance of interesting content used in digital promotions so that the display supports the delivery of training presentation materials. This research uses a qualitative approach. The data source for this research comes from questions in a questionnaire regarding the opinions of tourist village managers in Dander District, Bojonegoro Regency regarding making videos based on digital media content to improve promotional skills. This research aims to find out whether there is an increase in knowledge of learning outcomes obtained from training.